Advanced geospatial practices in natural environment resource management - Vohra, Rubina; Kumar, Ashish 1986- (Advances in geospatial technologies (AGT) book series, 2024)
The contents in the book emphasize not only on the issues pertaining to the environment but also presents the advanced management practices for the protection of varied fields related to environment.